2007
DOI: 10.1080/10942910600673636
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of Aqueous Carbohydrate Solutions at Different Temperatures and Concentrations

Abstract: Experimental viscosity values of sucrose, glucose, and fructose aqueous solutions in a large range of temperatures (0 to 85°C) and concentrations (10 to 60% w/w) that might be encountered in food processes were obtained in order to contribute to extending the available database of food properties. The temperature dependence of viscosity could be adequately described by the Arrhenius model, and the activation energy was well represented by a unique function of the solute volume fraction, valid for sucrose, gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
170
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(181 citation statements)
references
References 21 publications
7
170
1
3
Order By: Relevance
“…The temperature effect on viscosity will be much more pronounced at the higher concentrations occurring in natural nectars, e.g. 15.04 mPa s for a 50% sucrose solution at 208C [14]. Choices made by bees offered 20% w/w sucrose solutions with Tylose used to increase the viscosity to that of 27.5%, 31% and 34.5% w/w sucrose solutions: only data for individual bees observed during three successive feeder visits are included.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The temperature effect on viscosity will be much more pronounced at the higher concentrations occurring in natural nectars, e.g. 15.04 mPa s for a 50% sucrose solution at 208C [14]. Choices made by bees offered 20% w/w sucrose solutions with Tylose used to increase the viscosity to that of 27.5%, 31% and 34.5% w/w sucrose solutions: only data for individual bees observed during three successive feeder visits are included.…”
Section: Discussionmentioning
confidence: 99%
“…For experiments on both nectar temperature and viscosity, we had to use dilute artificial nectar in order to avoid overcrowding at the feeders, so the viscosity benefits from warming would be small. According to empirical data [14], the viscosity of the 10% sucrose used in our temperature experiment would decrease from 1.26 mPa s at 208C to 0.89 mPa s at 358C. However, we found significant effects on intake and preferences in the viscosity experiment, even at the relatively low viscosities used: these, assuming that air temperature averaged 208C, would have ranged from 1.96 mPa s for the 20% sucrose solution to approximately 4.34 mPa s for the 34.5% equivalent [14,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the flow behaviour of polydextrose and combination of maltodextrin+polydextrose syrups obeyed Hershel-Bulkley model. The viscosity of liquid depends on nature of solute, its molecular weight, molecular size and shape, solute-solvent interactions, and state of hydration (Nindo et al 2005;Telis et al 2007;Fennema 2005). …”
Section: Physicochemical Characteristicsmentioning
confidence: 99%